2023
DOI: 10.1002/jms.4908
|View full text |Cite
|
Sign up to set email alerts
|

Glycomics by ion mobility tandem mass spectrometry of chondroitin sulfate disaccharide domain in biglycan

Abstract: Biglycan (BGN), a small leucine-rich repeat proteoglycan, is involved in a variety of pathological processes including malignant transformation, for which the upregulation of BGN was found related to cancer cell invasiveness. Because the functions of BGN are mediated by its chondroitin/dermatan sulfate (CS/DS) chains through the sulfates, the determination of CS/DS structure and sulfation pattern is of major importance. In this study, we have implemented an advanced glycomics method based on ion mobility separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Thus, bisulfated saturated and trisulfated unsaturated disaccharides were detected. IMS MS/MS analysis demonstrated that at the CS/DS chains, non-reducing end 3-O-sulfated GlcA harbors a rare bisulfated motif that is possibly relevant to cancerassociated signaling [20]. In addition, biglycan can bear N-linked oligosaccharide chains bound into its central LRRs motifs, which are able to specifically modify biglycan-binding abilities [59].…”
Section: Biglycan Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, bisulfated saturated and trisulfated unsaturated disaccharides were detected. IMS MS/MS analysis demonstrated that at the CS/DS chains, non-reducing end 3-O-sulfated GlcA harbors a rare bisulfated motif that is possibly relevant to cancerassociated signaling [20]. In addition, biglycan can bear N-linked oligosaccharide chains bound into its central LRRs motifs, which are able to specifically modify biglycan-binding abilities [59].…”
Section: Biglycan Structurementioning
confidence: 99%
“…SLRPs interact with structural ECM molecules, cell membrane receptors, growth factors, and cytokines, as well as with their protein cores and GAG chains [16,17]. Notably, GAG chains can modify protein core-ligand interactions by introducing immense variability in their signaling [18][19][20]. A plethora of studies have demonstrated that SLRPs' expression is altered in tumors [21,22] and that by interacting with tyrosine kinase receptors or growth factors, they affect tumor behavior [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Several devices with different combinations of the applied electric field and separation technique are commercially available 21,22 . Numerous studies using IMS based on temporal-separation have been reported for the analysis of gangliosides, offering separation of isomeric ganglioside species and deep characterization of the ganglioside lipidome 16,17,[23][24][25][26][27][28][29][30][31][32][33][34] . In contrast, spatialseparation based IMS for gangliosides analysis has received limited attention 35 , despite its potential for increased sensitivity as shown in proteomics and lipidomics studies [36][37][38][39][40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies using IMS based on temporal-separation have been reported for the analysis of gangliosides, offering separation of isomeric ganglioside species and deep characterization of the ganglioside lipidome. ,, In contrast, spatial-separation based IMS for gangliosides analysis has received limited attention, despite its potential for increased sensitivity as shown in proteomics and lipidomics studies. Overall, ganglioside analysis approaches aim for high-confidence identifications, requiring accurate mass, MS/MS fragment information, and, ideally, matching database entries or a reference standard . Collision-induced dissociation (CID) and high-energy collisional dissociation (HCD) are the most commonly used ion activation methods for MS/MS lipid structural analysis.…”
Section: Introductionmentioning
confidence: 99%